Pengaruh Efektivitas Manajemen Dan Penempatan Terhadap Organizational Citizenship Behavior - Opiq Piqhi; Ranthy Pancasasti (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2022)
The study of Organizational Citizenship Behavior (OCB) is growing in line with the awareness that individual behavior affects the performance of individuals, groups, and organizations. Positive behavior of human resources (HR), both as superiors and subordinates, will create a comfortable work environment and in turn improve individual and organizational performance. This study aims to examine and analyze the factors that can improve organizational citizenship behavior. This research was conducted at dr. Drajat Prawiranegara (RSUD Serang), in November 2021. The population in this study were non-medical civil servants specifically group III (three) at Serang Hospital, totaling 793 people. The number of samples calculated by the Slovin formula, amounted to 82 people. Sampling was done by random sampling method, namely the sample was drawn from the population group at random with the help of Microsoft Excel software. This quantitative research includes survey research, using statistical tests, and PLS software version 3.0. The results of this study indicate that the effectiveness of management and employee placement has a significant direct effect on the organizational citizenship behavior of civil servants at Dr. Hospital. Drajat Prawiranegara Serang Regency. The findings in this study indicate that the effectiveness of management and employee placement has a significant effect on organizational citizenship behavior